Conservation of Pre-War Building in Muar and Batu Pahat, Johor - Omar, Abdul Jalil; Wan Yusoff, Wan Zahari; Azizan, Anim Zalina (Research in Management of Technology and Business, 2023)
Abstract: Malaysia is blessed with an old building which is known as a pre-war building that is full of history around the countries especially Johor. Some state of Malaysia, Penang, and Malacca have classified their pre-war building as a World Heritage Building under UNESCO but other states have not been classified as heritage buildings, but the locals still kept the pre-war building. Unfortunately, there is an incident that causes the pre-war building to be neglected, left to abandonment and led to the demolition. Therefore, this study is to identify the level of control by the local authority on towns like Muar and Batu Pahat, Johor on conserving the pre-war building. The study conducted a qualitative approach through interview method. The respondents involved in the interview is the 2 local authorities from Muar town (MPM) and Batu Pahat town (MPBP) on handling the pre-war building and 6 building owners of pre-war buildings. The data and information taken and analyzed as the data collected from the interview session with the respondents on guidelines, renovation process, building used, and cost for conserving the pre-war building. From the study, it can conclude that pre-war buildings were conserved with a proper guideline to conserve the pre-war building to preserve building value while retaining the charms of the historical buildings.Keywords: conservation, pre-war building, guideline